A qualidade do ambiente interno em áreas hospitalares: um estudo sobre o conforto, a ventilação e a renovação do ar - Cestavo, Rebeca Longatti (2021)
The relationship between architecture and air quality is studied at different times in history and nowadays it is in the spotlight due to COVID-19. Therefore, there is a direct connection between the building, the openings, the air renewal, and how these factors affect the users' health. In this sense, this dissertation's theme is "The Quality of the Internal Environment in Hospital Areas: A Study on Comfort, Ventilation and Air Renewal" whose specific objective is to analyze natural ventilation as a crucial factor for maintaining indoor air quality, mainly in the hospital environment, especially the wards, a place susceptible to contamination by airway infections. The methodological procedures started from the literature review, then we made a study of the ward at Sarah Kubitschek Hospital (Rio de Janeiro-RJ), from analysis, using computer simulations. This research demonstrated how important it is to use different ventilation types in multiple spaces at a hospital. It'd also shown the acknowledgment of air renewal as a promoter of the healthiness of the environment, and the well-being of patients, a strategy applied by João Filgueiras Lima in this hospital. The analysis had shown that such mechanisms have contributed to environmental comfort since factors analyzed such as wind speed, temperature, CO2 concentration, and air renewal reach the minimum parameters required by the standards. Therefore, in the ward of this hospital, air quality and the well-being of patients are guaranteed. The results obtained demonstrated the importance of designing space according to the norms and thinking about the user.